Fiber Bragg gratings : fundamentals and applications in telecommunications and sensing - Othonos, Andreas; Kalli, Kyriacos (Boston, Mass. : Artech House, 1999)
Provides a description of the principles and practical applications of Fibre Bragg gratings technology. The authors explain the underlying physics and practical aspects. Topics covered include photosensitivity; properties; inscribing grating; detailed applications coverage in both telecommunications and sensing and a look at the technology of this technology on the marketplace.
Introduction -- Photosensitivity in Optical Fibers -- Properties of Fiber Bragg Gratings -- Inscribing Bragg Gratings in Optical Fibers -- Fiber Bragg Grating Theory -- Applications of Bragg Gratings in Communications -- Fiber Bragg Grating Sensors -- Impact of Fiber Bragg Gratings.
Includes bibliographical references.
Keywords: Optical fibers; Bragg gratings; Optical detectors